Potret Kemiskinan dan Prostitusi dalam Dua Novel Feminisme Karya Artie Ahmad dan Ahmad Tohari - Angela Netasya; Muhammad Ismail Nasution (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
This study aims to describe: (1) portraits of poverty and prostitution in the novel Ronggeng Dukuh Paruk by Ahmad Tohari, (2) portraits and prostitution in the novel Sunyi Di Dada Sumirah by Artie Ahmad, (3) comparison of poverty and prostitution in the novel Ronggeng Dukuh Paruk by Ahmad Tohari and Sunyi Di Dada Sumirah by Artie Ahmad. This type of qualitative research with descriptive method. The research data are in the form of words, phrases, clauses, and sentences which are the problems of prostitution and problems through the narrator about the character, the character's speech, the character's actions, which are depicted in the novel. results Based on the research found the following data. First, in the novel Ronggeng Dukuh Paruk, the portrait of poverty is not fulfilled by clothing, food, and housing, low education, poor health, low income, and lack of employment opportunities. Acts of prostitution according to activities found and not recorded, according to the number of individuals and organized, according to the classification or location. The prostitutes in this novel get support from the surrounding environment. Second, in Sunyi Di Dada Sumirah's novel, the portrait of poverty shows that the lack of food and shelter, low education, and lack of employment opportunities force a person to become entangled in prostitution, not registered, organized, and located in entertainment venues/call houses, hotels, and karaoke places. However, the prostitute in the novel is not supported by the surrounding environment, which is considered a disgrace to life. Third, the comparison of poverty in the novel lies in people's awareness of the impact of poverty on life, Ronggeng Dukuh Paruk describes the poverty and destitution of the people of Dukuh Paruk not being a second burden as long as they can still be bullied, prostitution activities in this novel have environmental support. Meanwhile, in Sunyi Di Dada Sumirah's novel, it is always the root of the problem, so prostitution is their way of earning a living.